2004
DOI: 10.1002/ijc.20602
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐ and schedule‐dependent enhancement of zoledronic acid induced apoptosis by doxorubicin in breast and prostate cancer cells

Abstract: We investigated whether the combination of zoledronic acid and doxorubicin induced apoptosis of breast and prostate cancer cell lines, and if synergistic interaction was present. We investigated whether the levels of cell death altered depending on the sequence in which the drugs were administered and the possible mechanism of action responsible for the increased cell death following combined treatments. Breast and prostate cancer cells were treated with zoledronic acid alone, doxorubicin alone, or drugs in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 39 publications
(36 reference statements)
4
104
1
2
Order By: Relevance
“…This includes a combination with paclitaxel (Jagdev et al, 2001;Neville-Webbe et al, 2006), tamoxifen (Jagdev et al, 2000) and doxorubicin (Neville-Webbe et al, 2005). In our earlier study with ZA and chemotherapy drugs, we have similarly found that sequential administration of drugs is of paramount importance for inducing maximal (potentially synergistic) levels of apoptosis.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This includes a combination with paclitaxel (Jagdev et al, 2001;Neville-Webbe et al, 2006), tamoxifen (Jagdev et al, 2000) and doxorubicin (Neville-Webbe et al, 2005). In our earlier study with ZA and chemotherapy drugs, we have similarly found that sequential administration of drugs is of paramount importance for inducing maximal (potentially synergistic) levels of apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…before inhibition of the mevalonate pathway by ZA (Neville-Webbe et al, 2005) and subsequent apoptosis. In combination, ZA and letrozole have potential for synergistic induction of MCF7-Ca cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of doxorubicin combined with zoledronic acid induces apoptosis and inhibits proliferation of breast cancer cells in vitro and in vivo, with maximum effects detected when the chemotherapeutic agent is given 24 hours before the bisphosphonate (24,32,33). Here, we have shown the molecular pathways by which these two drugs interact to increase apoptosis, reduce proliferation, and ultimately inhibit MDA-MB-436 breast tumor growth in bone.…”
Section: Discussionmentioning
confidence: 79%
“…Zoledronic acid has been shown to synergistically increase cancer cell death when combined with doxorubicin, paclitaxel, or cyclophosphamide in breast cancer cells (24)(25)(26); paclitaxel, etoposide, cisplatinum, and irinotecan in lung cancer cells (27); and dexamethasone in myeloma cells (28) in vitro. Combining zoledronic acid (250 μg/kg) with the oral fluoropyrimidine UFT (20 mg) daily decreased the number of bone metastases compared with single agents in the 4T1 mouse mammary tumor model (29).…”
Section: Introductionmentioning
confidence: 99%